2020
DOI: 10.1111/epi.16700
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of osteoporosis medication on site‐specific fracture‐risk attenuation among adults with epilepsy

Abstract: Objective: The objective of this propensity score-matched, observational cohort study was to determine the effectiveness of osteoporosis medication on reducing the risk of non-trauma fracture (NTFx) among adults with epilepsy. Methods: Data from 01/01/2012 to 09/30/2015 was extracted from Optum Clinformatics Data Mart. NTFx risk attenuation from 12 months prior to 12 months after the individual's index date was examined for each group of adults ≥50 years of age as risk ratios (RRs with 95% confidence intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…To our knowledge, there are only few studies describing the efficacy of anti-osteoporosis treatment in patients on antiseizure drugs [31][32][33]. Lazzari et al (2013) performed a randomized controlled trial in male veterans with epilepsy [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are only few studies describing the efficacy of anti-osteoporosis treatment in patients on antiseizure drugs [31][32][33]. Lazzari et al (2013) performed a randomized controlled trial in male veterans with epilepsy [31].…”
Section: Discussionmentioning
confidence: 99%
“…Lacking a control group, it is unclear whether anti-osteoporosis treatment influenced the incidence of MOFs. Whitney (2020) adjusted for anti-osteoporosis treatment, by comparing five matched groups (n = 828 per group) by epilepsy status (with or without) and use of osteoporosis medication (no user, consistent user, or new user) [33]. His-study showed a twelve-month (non-traumatic) fracture risk attenuation in adults with epilepsy who were treated with anti-osteoporosis medication, especially in those who just started treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LEV had its own matched group (LEV matched ) and OXC had its own matched group (OXC matched ), pulling from the same comparator group (i.e., non‐ASM‐users without epilepsy). Propensity scores were computed based on age, sex, race/ethnicity, US region of residence, motor impairment, and baseline fracture using the PSMATCH procedure in SAS 9.4 (SAS Institute), as described previously 12,19 . The groups were each matched 1:2 (case:control) in a random fashion using a standard caliper of .25 standard deviations or less, without losing any participants from the LEV or OXC groups to limit bias.…”
Section: Methodsmentioning
confidence: 99%
“…Propensity scores were computed based on age, sex, race/ethnicity, US region of residence, motor impairment, and baseline fracture using the PSMATCH procedure in SAS 9.4 (SAS Institute), as described previously. 12,19 The groups were each matched 1:2 (case:control) in a random fashion using a standard caliper of .25 standard deviations or less, without losing any participants from the LEV or OXC groups to limit bias. Balance in matching was assessed using a standardized mean difference of .10 or less and compared using the chi-squared test for categorical variables or the independent t-test for continuous variables to ensure balance in matching.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Die Einleitung einer Abklärung und ggf. Therapie bei Verdacht auf Osteoporose ist im Sinne der Frakturprophylaxe sinnvoll [ 12 ].…”
Section: Nachbehandlungunclassified